Data Governance and Policy in Africa - Ndemo, Bitange; Ndung'u, Njuguna; Odhiambo, Scholastica; Shimeles, Abebe (Information Technology and Global Governance, 2023)
This open access book examines data governance and its implications for policymaking in Africa. Bringing together economists, lawyers, statisticians, and technology experts, it assesses gaps in both the availability and use of existing data across the continent, and argues that data creation, management and governance need to improve if private and public sectors are to reap the benefits of big data and digital technologies. It also considers lessons from across the globe to assess principles, norms and practices that can guide the development of data governance in Africa. The book will appeal to scholars and students of data governance, technology and public policy, as well as practitioners and policy makers.